1994
DOI: 10.1093/oxfordjournals.jbchem.a124631
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Biochemical Lesion, and Characteristic Response to Lipopolysaccharide (LPS) of a Cultured Macrophage-Like Cell Mutant with Defective LPS-Binding1

Abstract: We have previously isolated a lipopolysaccharide (LPS)-resistant mutant (named LR-9) of a cultured macrophage-like cell line, J774.1. This mutant had defective LPS binding [Hara-Kuge, S., Amano, F., Nishijima, M., and Akamatsu, Y. (1990) J. Biol. Chem. 265, 6606-6610]. In this study, we found that: (1) LPS-binding to parental J774.1 cells was dependent on a serum factor with a molecular weight of about 60 kDa, probably LPS binding protein (LBP); (2) LPS-binding to J774.1 cells was markedly reduced by treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…In the same experiment, the reference LPS induced TNF-␣ production in a concentration-dependent manner from 1 to 100 ng/ml and exhibited a plateau response at 100 ng/ml to 10 g/ml. In accordance with a previous report by Nishijima et al (27), LR-9 cells did not respond to the lower concentrations of LPS (1 to 100 ng/ml) and showed only a slight response to the higher concentrations (1 and 10 g/ml) (Fig. 3B).…”
Section: Expression Of Mcd14 By J7741 and Lr-9 Cells In Culturesupporting
confidence: 93%
See 1 more Smart Citation
“…In the same experiment, the reference LPS induced TNF-␣ production in a concentration-dependent manner from 1 to 100 ng/ml and exhibited a plateau response at 100 ng/ml to 10 g/ml. In accordance with a previous report by Nishijima et al (27), LR-9 cells did not respond to the lower concentrations of LPS (1 to 100 ng/ml) and showed only a slight response to the higher concentrations (1 and 10 g/ml) (Fig. 3B).…”
Section: Expression Of Mcd14 By J7741 and Lr-9 Cells In Culturesupporting
confidence: 93%
“…LR-9 cells were originally isolated from J774.1 cells as an LPS-resistant mutant with a defect in LPS binding (13) and later were reported to lack mCD14 (27). Therefore, we first compared mCD14 expression by J774.1 cells with that by LR-9 cells by flow cytometry.…”
Section: Expression Of Mcd14 By J7741 and Lr-9 Cells In Culturementioning
confidence: 99%
“…To test more specifically whether these effects can be entirely explained by the removal of CD14, advantage was taken of the LR-9 strain of J774 cells, which was selected for its resistance to LPS 16 and found to be deficient in the expression of CD14. 17 As shown in Figure 7, LR-9 cells are deficient in the surface expression of CD14 in comparison with the parental J774 cells. If the effects of PI-PLC treatment are a result of the removal of CD14, recognition of lipid-symmetric erythrocytes and apoptotic thymocytes by LR-9 cells should mimic that of PI-PLC-treated J774 cells.…”
Section: Resultsmentioning
confidence: 93%
“…It was reported that the complex of LPS and LPS binding protein interacted with the cell surface protein CD14 (22), and that this binding protein accelerated TNF-a production via high affinity binding sites (21). Thus, a certain serum component might be involved in the induction of TNF-a secretion by EP3 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena are due to the effect of the lipopolysaccharide binding protein present in the serum on TNF-a induction (20,21). It was reported that the complex of LPS and LPS binding protein interacted with the cell surface protein CD14 (22), and that this binding protein accelerated TNF-a production via high affinity binding sites (21).…”
Section: Discussionmentioning
confidence: 99%